In vitro study of effectiveness of plant extracts against rhizoctonia solani causing sheath blight disease on rice (Oryza sativa L.) / Nur Maryam Mohamed - Mohamed, Nur Maryam (Faculty of Plantation and Agrotechnology, 2018)
Rice is an important cereal crop affected by various fungal, bacterial and virus diseases. Sheath blight disease caused by Rhizoctonia solani is one of the destructive disease under favourable weather conditions in rice growing areas that ultimately causes high yield losses. The initial symptoms are the formation of irregular or oval greenish grey spots on the leaf sheath. The symptom of disease was observed by using pathogenicity test. The rice was planted in a greenhouse at UiTM Melaka, Jasin Campus with a variety of MR220 to observe the symptom of the disease. Application of plant extracts as an alternative to commercial insecticides provide an eco-friendly control method. The antifungal effect of two plant extract which are Aloe vera (Aloe) and Chromolaena odorata (Siam weed) against the pathogen R. solani was evaluated by dual culture method. All plant extracts showed effective results with a various degree of antimicrobial effect at the different concentration which are 0%, 25%, 50% and 100%. Aloe vera shows strong fungitoxicity at 25% and 100% concentration with 88.00% mean inhibition fungus growth. While, C. odorata showed strong fungitoxicity at 100% with 79.33% mean inhibition. The uses of fungicides to control the disease causes some adverse impacts like the development of resistance in the pathogen, residual toxicity, pollution in the environment, and high cost.